Cross‐tolerance in amphibians: Wood frog mortality when exposed to three insecticides with a common mode of action. (21st February 2013) - Hua, Jessica; Cothran, Rickey; Stoler, Aaron; Relyea, Rick
Abstract Insecticide tolerance and cross‐tolerance in nontarget organisms is often overlooked despite its potential to buffer natural systems from anthropogenic influence. We exposed wood frog tadpoles from 15 populations to three acetylcholine esterase‐inhibiting insecticides and found widespread variation in insecticide tolerance and evidence for cross‐tolerance to these insecticides. Our results demonstrate that amphibian populations with tolerance to one pesticide may be tolerant to many other pesticides. Environ. Toxicol. Chem. 2013;32:932–936. © 2013 SETAC